Gender-affirming Chest Surgery: A Prospective Series of 155 Consecutive Cases of Double Incision Mastectomy - Pierre G. Vico, MD, PhD; Salomé Salmon, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. Mastectomy is the first single surgery that transgender men and nonbinary people frequently undergo. We present a prospective series of 155 cases of double incision mastectomy (DIM) with nipple-areolar complex (NAC) graft. Methods:. From January 2019 to December 2022, 165 outpatients were operated on, and 155 are included in the study. We analyzed age, resection weight, blood loss, duration of the procedure, complications, and follow-up. The Student t test combined with the nonparametric Mann-Whitney U test was used for statistical analysis. If the P value was less than 0.05, the test was considered significant. Results:. A total of 111 (72.6%) patients experienced no complications. Complications (27.4%) were minor: 4 seromas, 8 hematomas, 10 partial necrosis of the NAC, and 8 depigmentation of the NAC. Thirteen patients presented axillary dog ears requiring secondary excision. Two patients had hypertrophic scars. No case of infection was observed. We find a statistically significant correlation between hematoma and perioperative blood loss (P < 0.05), and between dog ears requiring secondary procedure and body mass index (P < 0.001), weight of resection (P < 0.01), and blood loss (P < 0.001). Conclusions:. DIM with NAC graft is a safe, reliable, top surgery procedure. Complications are minor, and postoperative morbidity is low. This study shows a correlation between blood loss during surgery and postoperative hematoma, and between dog ears requiring a surgery and body mass index, weight of resection, and blood loss. This surgery gives nice aesthetic results enhancing patients’ quality of life by improving body image.